Transsacrococcygeal approach to ganglion impar: radiofrequency application for the treatment of chronic intractable coccydynia - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2016)
Objective: Coccydynia is defined as pain in the coccygeal region. Among the many causes of coccydynia, the most common cause is trauma as a result of falling on the buttocks, repetitive microtrauma, or childbirth. Several methods are currently used for the treatment of coccydynia, including nonsteroidal anti-inflammatory drugs, intrarectal manipulation, epidural injections, ganglion impar blocks, and radiofrequency treatment (RFT). Wemm and Saberski used the transacrococcygeal methods to reduce tissue trauma. RFT is a percutaneous minimally invasive procedure. In this study, we aimed to assess the effect of the transsacrococcygeal approach on ganglion impar RFT in patients with chronic coccydynia. Methods: We retrospectively examined the data of 41 patients at the Department of Anesthesiology and Reanimation, Faculty of Medicine, Maltepe University (Pain Clinic), between January 1, 2010, and December 31, 2012. Results: The mean age of the patients was 46.68 +/- 11.00 years (range 28-67 [46] years). The average pain duration was 3.10 +/- 1.37 years. The difference between visual analog scale scores of the pre-and postprocedure was statistically significant. In the examinations carried out in the sixth month of the treatment, 90.2% of patients had a successful outcome, whereas treatment failed in 9.8% of patients. According to our patients' data, most of them had pain due to a trauma, were female, and overweight. Visual analog scale difference between preprocedure and early postprocedure, preprocedure and first month, preprocedure and sixth month were statistically significant (P= 0.001). Conclusion: Based on the lower pain scores and low complication rates after the operations, the results suggest that application of RFT on ganglion impar by the transsacrococcygeal approach is an effective and safe method for the treatment of chronic coccydynia. Patient selection, technique, and experience are the most important factors affecting the success of this method.
Keywords: coccydynia; transsacrococcygeal approach; radiofrequency